10.70124 TRANSFORMASI SUNGAI MELALUI INISIATIF KEPEMUDAAN: STUDI KASUS PENGEMBANGAN EKOWISATA MUNCUL FUN TUBING OLEH KARANG TARUNA DI DESA ROWOBONI, KABUPATEN SEMARANG - Ilyas, Muhammad; Adjeng Indi Safirah; Erika Nurul Fitria; Sulthan Salman Zain; Kaana Eryma Awsa; Muhammad Ilyas; Rafika Desylia Athaya Rabani (Departemen Teknologi Pertanian Universitas Hasanuddin, 2026)
ABSTRACT This article analyzes the unique phenomenon of transforming a river into an ecotourism destination through youth initiatives. The main case study is Muncul Fun Tubing (MFT), a river tubing tourism site located in Dusun Muncul, Rowoboni Village, Banyubiru District, Semarang Regency. This research aims to examine the historical and managerial processes behind the development of MFT and to evaluate its social, economic, and environmental impacts.Using a qualitative approach with a case study design, data were collected through in-depth interviews with the managers, participatory observation, and document study. The study found that MFT originated from an unexpected initiative in 2007, when residents creatively used old tires to transport materials for repairing a damaged embankment. This activity later inspired the idea of tourism, which was formally managed by Karang Taruna Tirta Aji in 2016. The main findings highlight multidimensional impacts: economically, MFT generates significant income for youth managers and creates economic opportunities for local MSMEs. Ecologically, the use of the river as a tourism asset has fostered greater awareness of conservation and environmental cleanliness (Lemon8-app, 2023). Socially, MFT serves as a platform for youth empowerment, strengthens multi-actor collaboration (Karang Taruna, Village Government, Pokdarwis), and offers unique services such as therapy for individuals with autism and people with mental disorders (Prihadi, 2023; Radar Semarang, 2022). It is concluded that Muncul Fun Tubing represents a successful model of community-based tourism that transforms natural assets into sustainable economic and social resources through youth leadership.